A locus that contributes to colonization of the intestinal tract by Bacteroides thetaiotaomicron contains a single regulatory gene (chuR) that links two polysaccharide utilization pathways. - Cheng, Q (1992)
Previously, we isolated two Tn4351-generated mutants of Bacteroides thetaiotaomicron (46-1 and CS3) that were unable to grow either on heparin or on chondroitin sulfate. This phenotype was unexpected, since the heparin and chondroitin sulfate utilization pathways had appeared from earlier studies to be independent of each other. Mutants 46-1 and CS3 were also of interest because both were unable to compete successfully with wild-type B. thetaiotaomicron in the intestinal tracts of germfree mice. Thus, both appeared to have a colonization defect. We have now cloned the chromosomal locus in which the transposon insertions in 46-1 and CS3 occurred. Southern blot analysis showed that the Tn4351 insertions in 46-1 and CS3 were about 100 bp apart. Using complementation and insertional mutagenesis, we localized the region affected by the 46-1 and CS3 insertions to within 2.5 kbp. This DNA segment was sequenced and found to contain a 401-codon open reading frame (ORF1) and the N-terminal segment of a second open reading frame (ORF2), which was downstream of ORF1 and transcribed in the same direction. The deduced amino acid sequence of ORF1 showed significant homology to that of a putative positive regulator of an arylsulfatase gene in Klebsiella aerogenes. ORF2 was at least 381 amino acids long and did not exhibit homology to any proteins in the data bases searched. Transposon insertions in both mutants 46-1 and CS3 disrupted ORF1. The results of insertional mutagenesis and complementation experiments indicated that ORF2 was not essential for growth on chondroitin sulfate or heparin. Thus, the chondroitin sulfate-negative and heparin-negative phenotypes of 46-1 and CS3 appear to be due to the interruption of a regulatory gene encoded by ORF1 and not to a polar effect of the insertions on a downstream gene(s). The gene encoding ORF1 has been designated chuR, for regulation of chondroitin sulfate and heparin utilization. Transcriptional fusion studies showed that the expression of chuR occurred at the same level under inducing and noninducing conditions, in contrast to the regulated expression of structural genes of the chondroitin sulfate utilization system. chuR was not autoregulated, nor was its expression affected by a mutation (46-4) that eliminated the expression of all chondroitin sulfate utilization genes but did not affect the utilization of heparin.